2007
DOI: 10.1073/pnas.0707198104
|View full text |Cite
|
Sign up to set email alerts
|

Grass roots chemistry: meta -Tyrosine, an herbicidal nonprotein amino acid

Abstract: Fine fescue grasses displace neighboring plants by depositing large quantities of an aqueous phytotoxic root exudate in the soil rhizosphere. Via activity-guided fractionation, we have isolated and identified the nonprotein amino acid m-tyrosine as the major active component. m-Tyrosine is significantly more phytotoxic than its structural isomers o-and p-tyrosine. We show that mtyrosine exposure results in growth inhibition for a wide range of plant species and propose that the release of this nonprotein amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
192
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(201 citation statements)
references
References 27 publications
8
192
1
Order By: Relevance
“…These tRNA aminoacylation levels are comparable to those previously reported in other bacterial systems using similar methods, as is the observed increase in deacylated tRNA upon starvation (20)(21)(22). When the strains were grown under amino acid stress conditions in the presence of physiologically relevant levels of the natural noncognate PheRS substrate m-Tyr (3,23,24), levels of aa-tRNA Phe were 23% higher in the editing-deficient strain than in the wild type. These results also revealed that the cellular ratio of aminoacylated to deacylated tRNA increases significantly in the absence of PheRS editing, particularly under amino acid stress conditions ( Fig.…”
Section: Ablation Of Phers Editing Alters the Cellular Ratio Of Aminosupporting
confidence: 72%
“…These tRNA aminoacylation levels are comparable to those previously reported in other bacterial systems using similar methods, as is the observed increase in deacylated tRNA upon starvation (20)(21)(22). When the strains were grown under amino acid stress conditions in the presence of physiologically relevant levels of the natural noncognate PheRS substrate m-Tyr (3,23,24), levels of aa-tRNA Phe were 23% higher in the editing-deficient strain than in the wild type. These results also revealed that the cellular ratio of aminoacylated to deacylated tRNA increases significantly in the absence of PheRS editing, particularly under amino acid stress conditions ( Fig.…”
Section: Ablation Of Phers Editing Alters the Cellular Ratio Of Aminosupporting
confidence: 72%
“…3-5, and see Table 1). The article by Bertin et al (6) in this issue of PNAS adds significantly to this growing body of supportive literature.…”
mentioning
confidence: 84%
“…Does the plant avoid accumulation of the compound by secreting it almost as quickly as it is produced, in a manner similar to that of Sorghum species that produce the allelochemical sorgoleone only in root hairs that secrete it rapidly (13)? Apparently this is not the mechanism, because Bertin et al (6) indicate that although the dry weight of the root exudate consists of up to 43% m-tyrosine, it is also a relatively abundant metabolite of the root. Is the compound sequestered into intracellular or intercellular locations where it can do little or no harm?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the discrimination against o-Tyr is only ϳ24,000 under typical growth conditions and ϳ6,900 in the presence of 2.0 mM paraquat (much lower discrimination than against m-Tyr), kinetic discrimination against o-Tyr-AMP by SccytoPheRS may play a role in Phe codon quality control at biologically relevant levels, particularly in conditions that favor oxidation of intracellular Phe. Alternatively, the import of exogenous o-Tyr is a plausible scenario, as structurally similar m-Tyr has been shown to be produced and exported by certain plant species in order to shape the ecology of their environments and inhibit the growth of competitor species (22). Production and export of non-protein amino acids is an effective strategy for chemically shaping a competitive environmental niche, provided the producer has the means to prevent the cytotoxic incorporation of these species (for review, see reviewed see Ref.…”
Section: Limitation Of O-tyr-trnamentioning
confidence: 99%